Antifeedant and growth inhibitory effects of Annonaceae derivatives on Helicoverpa armigera (Hübner). (July 2019) - Souza, Camila Moreira de; Baldin, Edson Luiz Lopes; Ribeiro, Leandro do Prado; Santos, Thaís Lohaine Braga dos; Silva, Ivana Fernandes da; Morando, Rafaela; Vendramim, José Djair
Abstract: This study evaluated the sublethal effects of an ethanolic extract from seeds of Annona mucosa Jacq. (ESAM, major compound rolliniastatin-1) and a botanical insecticide based on the extract of Annona squamosa L. (10, 000 mg kg −1 of annonin as the primary active ingredient; Anosom ® 1 EC) at their previously estimated concentrations (LC50  = 411.55 and 312.08 mg kg −1, respectively) on the food intake and biological parameters of Helicoverpa armigera (Hübner), an important pest species that was recently introduced to Brazil. In a greenhouse trial, ESAM (as an emulsifiable concentrate formulation) and the botanical insecticide based on the extract of A. squamosa (Anosom ® 1 EC) caused larval mortality and a significant decrease in foliar consumption (>90%) after 168 h of exposure on soybean plants. An evaluation of the indices of food consumption, growth and food utilization indicated that ESAM and Anosom ® 1 EC, when incorporated into artificial media for third instar H. armigera larvae, significantly decreased the growth rate and reduced the efficiency of the conversion of ingested food into biomass. Additionally, ESAM and Anosom ® 1 EC extended the larval stage and significantly reduced the viability of the larval and pupal stages and the average weight of the 24-h-old pupae. In light of these findings, ESAM and the acetogenin-based commercial bioinsecticide Anosom ® 1 EC are potential alternative control measures for H. armigera . Highlights: Annonaceae derivatives caused adverse effects to the development of H. armigera . Annonaceae derivatives at sublethal concentration are not antifeedant agents. Larval mortality and decrease of foliar consumption was observed under greenhouse conditions. ESAM and commercial bioinsecticide Anosom ® 1 EC represent potential as alternative control measures for H. armigera.